Nursing teachers teaching about death: challenge in the academic process - Lima, Márcia Gabriela Rodrigues de; Nietsche, Elisabeta Albertina (Rev Rene, 2016)
Objective: to understand the strategy used by nursing teachers for teaching about death in theoretical and practical activities of the Nursing Course. Methods: qualitative research with 14 Nursing teachers, through sampling by data saturation in a public institution of higher education. A semi-structured interview was used for data collection and Content Analysis was performed. Results: the teachers believed to be relevant teaching about death, however, many do not do it, highlighting as a limitation the bond with the patient, death in childhood, the feelings, personal values and the absence of specific disciplines. Conclusion: the way death is perceived influences the approach of this theme in teaching Nursing.